Peran key opinion leader dalam pemasaran film bertema kekerasan seksual - Nurulita, Fadliyya Syifa; Primadini, Intan (Jurnal Komunikasi Profesional, 2021)
Violence against women does not only occur in the private sphere, but also in the public sphere, for example in the workplace and educational institutions. Bombshell, a based on true story movie raises the issue of violence against women in the workplace. Promoting movies on violence against women theme in a country that still adheres to a patriarchal system is not easy. However, in Indonesia, it turned out that this movie not only attracted a large audience, but also received positive reviews from various parties. That success can be achieved due to the Marketing Public Relations strategy carried out by Cinema XXI as its distributor. This study aims to find out the Marketing Public Relations strategy of Cinema XXI in promoting Bombshell. This study is a qualitative research and data is obtained through in-depth interviews. Based on the result of this study, it is known that in order to get positive coverage, Bombshell’s marketing campaign also aimed to shape perceptions as well as to educate the audience regarding the issue of violence against women in the workplace. Furthermore, there was a significant role of Key Opinion Leaders in creating awareness about the raised issues as well as inviting audiences to watch the movie. Keywords: Bombshell  ; Key Opinion Leader; Marketing Public Relations; Violence against Women.